A Study to Evaluate Nurse Led Intervention Regarding Home Care Management Among Tuberculosis Patients Attending Chest and TB OPD at PGIMS Rohtak - Neetu Sharma; Hemwati; Rajesh Gupta (International Journal of Emergency and Trauma Nursing and Practices, 2025)
Introduction: Tuberculosis is an infectious bacterial pathogen caused by the bacillus called Mycobacteriumtuberculosis, an acid-fast rode shaped bacillus 0.8–5 μm in length and 0.2–0.6 μm in thickness. Tuberculosis (TB) primarily impacts the lungs (pulmonary TB), but it can also affect other parts of the body (extra-pulmonary TB). It spreads through the air and causes damage to the lungs and various other organs. TB is a significant public health issue in India. Aim: To assess the knowledge of tuberculosis patients and to evaluate nurse led intervention regarding home care management among tuberculosis patients. Method: The study was conducted by using quantitative approach and pre- experimental one group pre-test and post-design on 80 patients by using non probability convenient sampling technique and Self- structured questionnaire was used to assess the knowledge of patients regarding tuberculosis. Result: The mean value of overall pre-test knowledge score was 1.70 and SD was 5.54 whereas the mean value of post-test was 17.175 and SD was 4.64. Mean difference between pre-test and post-test knowledge scoreobtained was 15.5 which is equal to table value at 0.05 level of significance. Conclusion: The study shows that health education program was very effective in improving knowledge of patients regarding tuberculosis.
Keywords: Intervention; Knowledge; education program; evaluate; management